Effects of silicon (Si) fertilization on gas exchange and production in Brachiaria - Sarto, Marcos Vinícius Mansano [UNESP]; Lana, Maria do Carmo; Rampim, Leandro; Rosset, Jean Sérgio; Inagaki, Adriano Mitio; Bassegio, Doglas [UNESP] (Southern Cross Publishing, 2016)
Calcium silicate (CaSiO3) applied to the soil may increase Si content in the soil and plants, as well as reduce sweating and increase water use efficiency. In this study, we aimed to investigate whether the application of CaSiO3 increased Si content in plants and interfered with gas exchange and production components in Brachiaria. The experiment was performed using 8-L plastic pots in a greenhouse. Treatments were arranged in a randomized block design in a 3 × 5 factorial: three soils (Rhodic Acrudox, Rhodic Hapludox, and Arenic Hapludult) and five silicate rates (0, 1, 2, 4, and 6 t ha-1 of CaSiO3/MgSiO3) were used; four replications were performed. CaSiO3 application to the soil increases Si concentration in the leaves. Si in plants reduces internal CO2 concentration and increases the efficiency of water use and instantaneous carboxylation efficiency. In soils with low pH and a high Al+3 level, which is toxic, reduction in plant sweating increases the intrinsic efficiency of water use in Brachiaria. Si helped to alleviate the toxic effects of Al+3.
Keywords: Calcium silicate; Efficient use of water; Intercellular CO2 concentration; Transpiration